Role of IL-17A on resolution of pulmonary C. neoformans infection. - Karen L Wozniak; Sarah E Hardison; Jay K Kolls; Floyd L Wormley (PLoS ONE, 2011)
The current studies evaluated the role of interleukin (IL)-17A in the induction of protective immunity against pulmonary cryptococcosis in mice. Protection against pulmonary infection with C. neoformans strain H99γ was associated with increased IL-17A production. Signaling through the IFN-γ receptor (R) was required for increased IL-17A production, however, a Th17-type cytokine profile was not observed. Neutrophils were found to be the predominant leukocytic source of IL-17A, rather than T cells, suggesting that the IL-17A produced was not part of a T cell-mediated Th17-type immune response. Depletion of IL-17A in mice during pulmonary infection with C. neoformans strain H99γ resulted in an initial increase in pulmonary fungal burden, but had no effect on cryptococcal burden at later time points. Also, depletion of IL-17A did not affect the local production of other cytokines. IL-17RA⁻/⁻ mice infected with C. neoformans strain H99γ survived the primary infection as well as a secondary challenge with wild-type cryptococci. However, dissemination of the wild-type strain to the brain was noted in the surviving IL-17RA⁻/⁻ mice. Altogether, our results suggested that IL-17A may be important for optimal protective immune responsiveness during pulmonary C. neoformans infection, but protective Th1-type immune responses are sufficient for protection against cryptococcal infection.